Social Identity of Football Supporter’s Given (Phenomenology Study to Supporter of Pasoepati in Indonesia) - Suryo Putro, Waskito Aji (JURNAL PEDAGOGIK OLAHRAGA, 2017)
Abstract:Pasoepati  is  a  group  of  supporter  that  supporting  to  the Persis Football Club  of  Solo.  Pasoepati  is  a  phenomenon  group  which  is  really  complex. Marginally,  the  social  identity  of Pasoepati,  as  a  group  or  a  community, makes them different with other groups of supporters in Indonesia. Pasoepati appeared in 2000s  century  in  the  hard  social  context  because of  the  existence  of  gangs  in  that time.  And  finally,  Pasoepati  capable  to  get  a  kind  of  sympathy  of  people  in Solo  and  Indonesia,  as  the  supporter which  is has politeness  and  sportive,  in conveying  a  support.  Pasoepati appears  in  political  and  cultural  context  of  supporter institution,  but  once  Pasoepati  answers  it  by  a  group  that  has  a  cultural  basic without institution.Furthermore, this study is aim to know the construction of  Pasoepati social identity in appearance of history context. Besides that, this study aim to know how Pasoepati represents the sportive support in football. This  study  applies  qualitative  method.  The  approach  that  used  is phenomenology.  The  researcher  knows  that  getting  the  comprehensive understanding about Pasoepati, phenomenology is the more appropriate approche. Besides, by applying that approach the researcher tries to describe the data  in  perspective  subject  of  the  study.  Therefore,  the  researcher  gets  directly participation in the field and tries to as near as possible to the subject of the study.In  this  study,  the  researcher  uses  perspective  theory  identity. In practicing in the field and presenting the data, the researcher  uses  phenomenology  theories which  are  established  by Mostakas.  In which, the fact in the field is presented in the various and qualified way.   The  result  of  the  study  gets  some  political,  economical, social and  cultural phenomena,  which  built  the  social  identity  of  Pasoepati.And the conclusion is,  the researcher understands  the representation  is done by Pasoepati is good expecially  in giving the sportive support. Pasoepati  is a group  that ready  to acculturate  the habitual or culture from  the  outside  which  is  thought  well  and  appropriate  to  keep  the  existence. However, Pasoepati  still  aware  that  the  acculturation  is  done  should  still  in  the line for keeping the identity social that was built.          The key words: social identity, supporter, football, sportive, Pasoepati